High Levels of Within-Host Variations of Human Papillomavirus 16 E1/E2 Genes in Invasive Cervical Cancer - Hirose, Yusuke; Yamaguchi-Naka, Mayuko; Onuki, Mamiko; Tenjimbayashi, Yuri; Tasaka, Nobutaka; Satoh, Toyomi; Tanaka, Kohsei; Iwata, Takashi; Sekizawa, Akihiko; Matsumoto, Koji; Kukimoto, Iwao (Frontiers in Microbiology, 2020)
Human papillomavirus type 16 (HPV16) is the most common HPV genotype found in invasive cervical cancer (ICC). Recent comprehensive genomics studies of HPV16 have revealed that a large number of minor nucleotide variations in the viral genome are present in each infected woman; however, it remains unclear whether such within-host variations of HPV16 are linked to cervical carcinogenesis. Here, by employing next-generation sequencing approaches, we explored the mutational profiles of the HPV16 genome within individual clinical specimens from ICC (n = 31) and normal cervix (n = 21) in greater detail. A total of 367 minor nucleotide variations (167 from ICC and 200 from the normal cervix) were detected throughout the viral genome in both groups, while nucleotide variations at high frequencies (>10% abundance in relative read counts in a single sample) were more prevalent in ICC (10 in ICC vs. 1 in normal). Among the high-level variations found in ICC, six were located in the E1/E2 genes, and all of them were non-synonymous substitutions (Q142K, M207I, and L262V for E1; D153Y, R302T, and T357A for E2). In vitro functional analyses of these E1/E2 variants revealed that E1/M207I, E2/D153Y, and E2/R302T had reduced abilities to support viral replication, and that E2/D153Y and E2/R302T failed to suppress the viral early promoter. These results imply that some within-host variations of E1/E2 present at high levels in ICC may be positively selected for and contribute to cervical cancer development through dysfunction or de-stabilization of viral replication/transcription proteins.